Type study of one species described in the genus Ceracea - Vera F. Malysheva (Acta Mycologica, 2013)
The type revision of one species known as Ceracea aureofulva Bres. is presented. New combination Cerinomyces aureofulvus (Bres.) Malysheva is proposed. The detailed taxonomic description and illustration of the specimen are given.